Preconception analysis of evolution on pre-service biology teachers using certainty of response index. Issue 2 (February 2019) - Helmi, H; Rustaman, N Y; Tapilow, F S; Hidayat, T
Abstract: Preconception of students about evolution often related to knowledge got from environment and resource surrounding without scientific base. Therefore, it was needed badly to detect misconception on students before the courses so as to determine the direction to overcome it. This qualitatively descriptive study was conducted to get clear picture of student conception in evolution before the course held. And also the probability of misconception. A number of students from Islamic University in Cirebon was involved as participants (n=54). The instrument used consisted of 10 multiple choice with certainty of response index (CRI) and individual interview to analyze the reasons or the causes of misconception. Research results show that the percentages of understand concept (UC), not understand concept (NUC), guessing (G) and misconception (M). It was also found that the percentage of misconception among the students is relatively high (35.7%) from the whole answers given to the test items tested. The highest misconception detected was in Phylogenetic topic. Based on the individual interview it was detected that they have difficulties in certain concepts in sequent: phylogenetic (50%); the origin of living things (24%), natural selection (3.7%) and evolutionary theory (16.6%).